ROMP (co)polymers with pendent alkyne side groups: post-polymerization modification employing thiol–yne and CuAAC coupling chemistries - van Hensbergen, J.; Burford, R.; Lowe, Andrew (R S C Publications, 2014)
The synthesis of a series of copolymers via ring-opening metathesis polymerization (ROMP) containing pendent trimethylsilyl-protected alkyne functional groups is described. Deprotection of the protected ynes yields copolymers with free alkyne functionality that can be utilized as a reactive handle for thiol–yne (TYC) and Cu-catalyzed alkyne–azide coupling (CuAAC) either independently or together.